Biologically active peptides from marine proteobacteria: Discussion article - Komal Anjum (Open Journal of Bacteriology - Peertechz Publications, 2021)
Marine bioactive peptides are deliberated as an abundant source of natural products that may give long-hual fitness, in comparison to other resources. Numerous literature concerning bioactive peptides from marine proteobacteria has been summarized, which shows the possibleness of therapeutic efficacy comprehensive wide spectra of bioactivities against many infectious agents. Their antimicrobial, antitumor, antiviral, and other bioactivities have gained an attention for the medicine development toward a new flow of drug explicate, for therapy and control of several diseases. Nonetheless, the execution of the action of several peptides has been still unexplored. So in this glance, this mini-review is focused on some peptides by which they intervene with microbial infection. This compilation is one of the main extract to be implicit particularly for the conversion of biomolecules into desired medicines.